2013
DOI: 10.1186/1755-7682-6-30
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of cricket – view from South Asia

Abstract: Although cricket has origins in the British Empire, it is followed as a religion in South Asia, probably due to the influence of the former during their rule. The sport is equally popular among all groups of the society, and is not subject to gender or age constraints. It marks the epitome of reverence and is considered a battle for self-esteem, not only for those playing, but for those watching as well. The intensity of emotional attachment with this sport renders certain public health benefits as well as dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…It is unlikely that this ethnicity bias is due to the geodemographic racial distribution of the general population, as the BSA population across England and Wales is increasing (Department for Education, 2019;ECB, 2018). Furthermore, due to the popularity of cricket amongst the BSA community (ECB, 2018;Sheikh et al, 2013), combined with the overrepresentation of BSA players in the TDPs, it could be argued that a lack of potential talent is unlikely to be the reason for this under-representation. Hylton (2010) states that myths and stereotypes surrounding BSAs' exclusion from elite sports are typically framed as such: (a) socio-cultural influences; (b) role models and sporting competence; (c) religion and physicality; and, (d) diet and nutrition.…”
Section: Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that this ethnicity bias is due to the geodemographic racial distribution of the general population, as the BSA population across England and Wales is increasing (Department for Education, 2019;ECB, 2018). Furthermore, due to the popularity of cricket amongst the BSA community (ECB, 2018;Sheikh et al, 2013), combined with the overrepresentation of BSA players in the TDPs, it could be argued that a lack of potential talent is unlikely to be the reason for this under-representation. Hylton (2010) states that myths and stereotypes surrounding BSAs' exclusion from elite sports are typically framed as such: (a) socio-cultural influences; (b) role models and sporting competence; (c) religion and physicality; and, (d) diet and nutrition.…”
Section: Ethnicitymentioning
confidence: 99%
“…However, as cricket's origins trace back through the British Empire, which covered large parts of the subcontinent at the turn of the twentieth century, it is unsurprising that there is high participation across most South Asian countries today. From a socio-environmental perspective, it has been suggested that cricket is followed like a "second religion" in the subcontinent due to the extreme levels of passion and enthusiasm for the game (Sheikh, Ali, Saleem, Ali, & Ahmed, 2013), and that like religion, cricket is deeply entangled within everyday conceptions of cultural identities in many minority ethnic communities (Fletcher, 2015). Therefore, it could be argued that the motives for normal ethnic exclusion put forth by Hallmann and Breuer (2014) may not apply for British South Asian (BSA) cricketers in England and Wales, as cricket appears to be socially valued by both white British (WB) and BSA cultures.…”
Section: Introductionmentioning
confidence: 99%